Disposable non-enzymatic blood glucose sensing strip based on nanoporous platinum particles. (March 2018) - Lee, Saram; Lee, Joungmin; Park, Sejin; Boo, Hankil; Kim, Hee Chan; Chung, Taek Dong
Graphical abstract: Highlights: An introduction of disposable non-enzymatic electrochemical glucose sensor using chemically reduced nanoporous Pt particles. An acceptable performance in phosphate-buffered saline (PBS) solution, even in human whole blood. Shed light on finding the path to industrialization of non-enzymatic glucose sensor. Abstract: We introduce a disposable non-enzymatic glucose sensor that uses nanoporous Pt instead of enzymes since nanoporous Pt is an ideal electrode material for the electrochemical sensing of glucose. In this work, a nanoporous Pt electrode composed of Pt nanopore-containing particles is formed by simply dispensing a mixture of nanoporous Pt particles and a binding polymer onto a conducting circuit screen-printed on polyimide film; the nanoporous Pt particles were prepared by chemically reducing a Pt precursor in a reverse-micellar phase. This dispensing method is more cost-effective and scalable for mass production in comparison to electroplating. Electrodes based on nanoporous Pt particles dispensed in the manner were tested as non-enzymatic disposable glucose sensors; they exhibited good linearities and acceptable performance in phosphate-buffered saline (PBS) solution at pH 7.4. In human whole blood, the sensors also properly responded to glucose levels. Error grid analysis reveals that most of the data are distributed regions A and B (A: 64%, A + B: 98%).